2013
DOI: 10.5812/ircmj.2209
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary Plasmacytoma of the Nasal Cavity Report of Three Cases With Review of the Literature

Abstract: Extramedullary plasmacytoma is a rare neoplasm characterized by monoclonal proliferation of plasma cells. Most lesions occur in the head and neck, primarily in the upper aerodigestive tract. The nasal cavity and nasal septum are the most common sites of occurrence. In this report, three patients admitted in our clinic with history of nasal obstruction and/or epistaxis. Patients were diagnosed with extramedullary plasmacytoma and mass were completely excised. This entity usually occurred in 5th-6th decade of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 10 publications
3
19
0
3
Order By: Relevance
“…SN‐EMP tends to present insidiously with nonspecific obstructive symptoms delaying timely diagnosis. Patients typically present in the 5th to 8th decade of life . Consistent with prior studies, we found a mean age at diagnosis of 61.3 years with a standard deviation of 15.9 years in our SN‐EMP cohort.…”
Section: Discussionsupporting
confidence: 90%
“…SN‐EMP tends to present insidiously with nonspecific obstructive symptoms delaying timely diagnosis. Patients typically present in the 5th to 8th decade of life . Consistent with prior studies, we found a mean age at diagnosis of 61.3 years with a standard deviation of 15.9 years in our SN‐EMP cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Soft tissue plasmacytoma has a significant sex-related susceptibility, with a mean male/ female ratio of 2.7. In this study males were more frequently affected, consistent with data previously reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 92%
“…It accounts for 1 % of all head and neck malignant tumors. The most common sites of EMPs are the nose, paranasal sinuses, nasopharynx and tonsils, but it can also occur in the gastro-intestinal tract, CNS, urinary bladder, thyroid, testes, parotid gland and lymph nodes [3][4][5][6]. Men are more commonly affected, with a median age at diagnosis of 50-60 years.…”
Section: Introductionmentioning
confidence: 99%
“…In our patient, this symptom was correlated with a benign lesion in the first observation and secondly, it was symptomatic of an ENP in early stage. In both observations, the patient never presented any other symptoms associated with the nasal obstruction such as epistaxis (12,13), rhinorrhea (12), anosmia (13), nasal discharge (12,13) or sudden episode of obstructive sleep apnea syndrome (14). These symptoms have been widely described in patients affected from nasal cancer (12)(13)(14).…”
Section: Discussionmentioning
confidence: 74%